Material didáctico y la dificultad para aprender geometría en niños de educación inicial, subnivel 2 - Merchán Espinoza, Daniela Belén; Macas Quezada, Johanna Leticia (Machala, 2022)
The present research work is entitled: "DIDACTIC MATERIAL AND THE UNDERSTANDING OF GEOMETRIC FIGURES IN CHILDREN OF INITIAL EDUCATION, SUBNIUM II"; which has as hypothesis raised about: There is a relationship between the didactic material and the comprehension of geometric figures in children of initial education of sublevel 2; this problematic starts from the direct observation that has been made during the pre-professional practices where it is evident that the children of the Simon Bolivar School present difficulty to identify the geometric figures through the use of the didactic material; For this reason, there have already been antecedents that support this problem that mention that the educators do not share with the infants the didactic materials because the educational institution does not have the necessary resources that are useful for the apprentices; for this reason we have proposed the following objective: "To determine the relationship that exists between the didactic material and the comprehension of geometric figures in children of initial education sublevel 2". The approach used is quantitative; the type of study used is descriptive; for this purpose, we applied the following instruments: the observation guide directed to 99 children and the interview with 3 educators in order to collect data and prove the existence of the problem. After analyzing them, we proposed a solution that consisted of providing training workshops for teachers on the correct use and handling of didactic material for the teaching of geometric figures. In conclusion, we determined the relationship that exists between the didactic material and the understanding of geometric figures, in order to improve the teaching-learning process in early childhood education, where the most important thing is that through the recognition of geometric figures, children develop skills and abilities, thus enhancing mathematical logical thinking; What helped us most to determine this was the application of the research instruments which allowed us to demonstrate the difficulties that the children have when manipulating the didactic material and not being able to recognize the geometric figures. The most difficult part was the search for information that supports the relationship between the didactic material and the comprehension of geometric figures in children in early childhood education level 2.
El presente trabajo de investigación esta titulado: “MATERIAL DIDÁCTICO Y LA COMPRENSIÓN DE FIGURAS GEOMÉTRICAS EN LOS NIÑOS DE EDUCACIÓN INICIAL, SUBNIVEL II”; la cual tiene como hipótesis planteada acerca de: Existe relación entre el material didáctico y la comprensión de figuras geométricas en niños de educación inicial de subnivel 2; esta problemática parte desde la observación directa que se ha realizado durante las prácticas pre-profesionales donde se evidencia que los niños de la Escuela Simon Bolívar presentan dificultad para identificar la figuras geométricas a través del uso del material didáctico; para ello ya han existido antecedentes que sustentan esta problemática que mencionan que las educadoras no comparten con los infantes los materiales didácticos debido que la institución educativa no cuenta con los recursos necesarios que son de utilidad para los aprendices; por ello hemos planteado el siguiente objetivo: “ Determinar la relación que existe entre el material didáctico y la comprensión de figuras geométricas en niños de educación inicial subnivel 2”. El enfoque empleado es de carácter cuantitativo; el tipo de estudio utilizado es descriptiva; para ello se aplicó los instrumentos que han sido; la guía de observación dirigida a 99 niños y la entrevista planteada a 3 educadoras con finalidad recolectar datos y comprobar la existencia del problema. Luego de haberlos analizado planteamos una solución que consiste en brindar talleres de capacitación dirigido a las docentes acerca del uso y manejo correcto del material didáctico para la enseñanza de figuras geométricas. Concluyendo así que se determinó la relación que existe entre el material didáctico y la comprensión de figuras geométricas, para así mejorar el proceso de enseñanza aprendizaje en niños de educación inicial; donde lo más importante de todo aquello es que los infantes a través del reconocimiento de figuras geométricas desarrollan habilidades y destrezas logrando así potenciar el pensamiento lógico matemático; lo que más nos ayudó a determinar aquello fue la aplicación de los instrumentos de investigación el cual nos permitió evidenciar las dificultades que presentan los niños al manipular el material didáctico y no lograr reconocer las figuras geométricas y considerándose lo más difícil fue la búsqueda de información que fundamente la relación del material didáctico y la comprensión de figuras geométricas en niños de educación inicial subnivel 2.
Keywords: MATERIAL DIDACTICO; FIGURA GEOMETRICA; MANIPULACION